Emicizumab, the bispecific antibody to factors IX/IXa and X/Xa, potentiates coagulation function in factor XI‐deficient plasma in vitro. (10th December 2018) - Minami, H.; Nogami, K.; Yada, K.; Ogiwara, K.; Furukawa, S.; Soeda, T.; Kitazawa, T.; Shima, M.
Summary: Essentials Emicizumab mimics factor (F)VIIIa cofactor function, augments the intrinsic tenase activity. We assessed the emicizumab‐driven hemostatic function in FXI‐deficient plasmas. Emicizumab improved the coagulation potentials in severe FXI‐deficient plasma. Emicizumab may provide a possibility for clinical application in patients with FXI deficiency. Summary: Background: Patients with factor (F)XI deficiency commonly present with markedly prolonged activated partial thromboplastin times (APTT), although bleeding phenotypes are heterogeneous. Emicizumab, a bispecific monoclonal antibody to FIX/FIXa and FX/FXa, mimics FVIIIa cofactor function on phospholipid (PL) surfaces. Antibody reactions were designed, therefore, to augment mechanisms during the propagation phase of blood coagulation. Aim: To assess emicizumab‐driven hemostatic function in FXI‐deficient plasmas. Methods and Results: Standard ellagic acid (Elg)/PL‐based APTTs of different FXI‐deficient plasmas ( n = 13; FXI activity, < 1 IU dl −1 ) were markedly shortened dose dependently by the presence of emicizumab. To further analyze the effects of emicizumab, clot waveform analysis (CWA) in FXI‐deficient plasmas with emicizumab, triggered by tissue factor (TF)/Elg demonstrated improvements in both clot times, reflecting the initiation phase, and coagulation velocity, which represents the propagation phase. Emicizumab also enhanced the TF/Elg‐triggered thrombin generation in FXI‐deficient plasmas dose‐dependently although the degree of enhancement varied in individual cases. Thrombin generation with either FVII‐deficient plasma or FIX‐deficient plasma treated with anti‐FXI antibody showed little or no increase by the co‐presence of emicizumab, suggesting that the accelerated thrombin generation in FXI‐deficient plasmas by emicizumab should depend on the FIXa‐involved coagulation propagation initially triggered by FVIIa/TF. The ex vivo addition of emicizumab to whole blood from three patients with severe FXI deficiency demonstrated modest, dose‐dependent improvements in Ca 2+ ‐triggered thromboelastograms (NATEM mode). Conclusion: Emicizumab appeared to improve coagulation function in severe FXI‐deficient plasma, and might provide possibilities for clinical application in patients with FXI deficiency.